Segmentation based Kidney Tumor Classification using Deep Neural Network - Mehedi, Md Humaion Kabir; Haque, Ehteshamul; Radin, Sameen Yasir; Ur Rahman, Md. Abrar (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2022